Optimization of preparation conditions for activated carbons from coconut husk using response surface methodology - Tan, Ivy A. W.; Abdul Latif, Ahmad; Hameed, Bassim Hamid (Elsevier Ltd, 2008)
Coconut husk was used to prepare activated carbon using physiochemical activation method, consisted of potassium hydroxide (KOH) treatment and carbon dioxide (CO2) gasification. The effects of the preparation variables which were activation temperature, activation time and chemical impregnation (KOH:char) ratio on the adsorption capacity on methylene blue dye and carbon yield were investigated. Based on the central composite design (CCD), a two factor interaction (2FI) model and a quadratic model were respectively developed to correlate the preparation variables to the adsorption capacity and yield. From the analysis of variance (ANOVA), the most influential factor on each experimental design response was identified. The predicted adsorption capacity and yield after process optimization was found to agree satisfactory with the experimental values. The optimum conditions for preparing activated carbon from coconut husk were found as follows: activation temperature of 816 °C, activation time of 1 h and KOH:char ratio of 3.9.